Hepatitis B awareness and vaccination status among first year medical students - Giri, Mamata Rani; Panda, Jay Kumar; Sahoo, Arun Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Hepatitis B virus is the major cause of chronic liver disease and hepatocellular carcinoma. In India 2-4% individual are chronic carrier of HBV. Hepatitis B vaccine which is highly safe and effective in prevention of HBV infection and its serious complication. Medical students are susceptible to HBV infection during exposure to clinical cases & different procedure. The objective of the study was to assess the knowledge regarding hepatitis B disease among the first year MBBS students and to know the vaccination status against Hepatitis B among the students. Methods:It was a cross sectional study undertaken in the month of November 2013 among the first year MBBS students taken admission in academic session 2013-14 of VSS Medical College Burla, Sambalpur. All the first year MBBS students who were present in the community medicine theory classes on the day of data collection included as study subjects. Data were collected in a pre-designed self-administered questionnaire & it was analysed with MS excel 2007. Results: Out of 150 students, 110 students were participated, 95 students (86.3%) had knowledge regarding the causative agent and organ involvement. 76 students (69%) had known about the modes of transmission. 38% knew its incubation period. People who are at risk was known to 25(22.7%) students. 78 (70.9%) students had known about the importance of vaccination. 57 (51.8%) were vaccinated & 17(15.4%) students were incompletely vaccinated. Conclusions:The knowledge regarding various aspects of Hep-B among the first year medical students is inadequate. The vaccination status is poor. The non-vaccinated students should be completely vaccinated as early as possible before their clinical exposure.